Effects of the Latex of Synadenium grantii Hook F. (Euphorbiaceae) on a Preclinical Model of Canine Prostate Cancer - Brito, Eric Saymom Andrade; Prado, Laís Di Paulie Taborda; Araújo, Liana Késia Costa; Arnhold, Emmanuel; Matos, Moema Pacheco Chediak; de Paula, Joelma Abadia Marciano; Ramos, Luciana Machado; Fonseca-Alves, Carlos Eduardo; de Moura, Veridiana Maria Brianezi Dignani (Frontiers in Veterinary Science, 2021)
Prostatic carcinoma (PC) stands out in terms of its occurrence, pathophysiology, and unfavourable prognostic in human and dogs. Natural drugs represent an integrative potential to conventional antineoplastic treatments. In this context, Synadenium grantii bioproducts have been empirically used in different parts of Brazil for the integrative treatment of prostate cancer in humans. However, no scientific evidence is available on S. grantii antitumor effects. Therefore, this study aimed to investigate bioactive compounds in S. grantii latex using high-resolution mass spectrophotometry (HRMS) and evaluate its cytotoxic effects on primary canine PC cell cultures. Besides that, we evaluated the effects of S. grantii latex on angiogenesis using a chorioallantoic membrane (CAM) model of embryonated chicken eggs. In the HRMS, four fragments of phorbol ester were identified as potential bioactive compounds. In an MTT assay, two canine prostatic carcinoma cell lines (PC 1 and PC2) showed decrease in tumour cell count, with an IC50 of 0.8469 mg/ml for PC1, and 0.6068 mg/ml for PC2. The CAM assay showed a positive correlation between high dilution concentrations and antiangiogenic effect (p<0.05%). Reductions in vessel number and volume were macroscopically observed. Histomorphology, besides the reduction in vessels (p<0.05%), showed several degrees of inflammation, fibroplasia, and necrosis of the CAM. In conclusion, S. grantii latex has phorbol esters in its composition, and its aqueous solution has cytotoxic effect on canine metastatic PC cells in vitro, and a dose-dependent effect on in vivo angiogenesis in embryonated chicken egg CAM.